The use of human suprapubic bladder catheter to manage obstructive urolithiasis in a Saanen Buck - Khairuddin, Nurul Hayah; Hiew, Mark Wen Han; Ahmad Affandi, Syahirah; Muhamad, Azim Salahudin; Haron, Nur Asyikin; Radzi, Rozanaliza; Chen, Hui Cheng; Vythilingam, Ganesh (NRCT, 2021)
A three-year-old Saanen buck presented with a complaint of stranguria for 24 hours. A physical examination revealed that the perineal urethra was turgid, swollen, and tender, and the urinary bladder was distended. The goat was diagnosed with obstructive urolithiasis. A percutaneous tube cystotomy technique was performed to relieve progressive urinary bladder distension. Using a human suprapubic urinary bladder catheter system, the technique was performed twice due to the recurrence of the blocked urethra. Following drainage of the urine, all vital parameters returned to normal. After surgical cystotomy, an intraoperative observation revealed the urinary bladder was filled with white sandy urolith, which was removed through the surgical tube cystotomy technique. A preoperative urethrogram and cystourethrogram were performed to assess the presence of urolith along the urinary tract. The case outcome supports using a human suprapubic urinary bladder catheter as a rapid method for immediate relief of a distended urinary bladder in a goat.